2012
DOI: 10.1021/ac300309c
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Paper-Based Analytical Device for Particulate Metals

Abstract: A microfluidic paper-based analytical device (μPAD) fabricated by wax printing was designed to assess occupational exposure to metal-containing aerosols. This method employs rapid digestion of particulate metals using microliters of acid added directly to a punch taken from an air sampling filter. Punches were then placed on a μPAD, and digested metals were transported to detection reservoirs upon addition of water. These reservoirs contained reagents for colorimetric detection of Fe, Cu, and Ni. Dried buffer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
220
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(252 citation statements)
references
References 33 publications
(42 reference statements)
4
220
0
4
Order By: Relevance
“…The limit of quantification (LOQ) was estimated at 40 ppm, which was the minimum concentration that could be distinguished by the image processing software when the threshold of the color intensity was adjusted to the minimum value of zero, which was the intensity of the blank. The LOQ was comparable to that reported by Mentele et al 16 (1.5 μg in 30 μL, 50 mg L -1 ) while Asano et al found a lower LOQ (13.8 μM, 0.771 mg L -1 ) using a paper device with test spots where no diffusion happened since a single spot was used as a reservoir. 23 Thus, the spot-type paper device was preferable for enhancing the sensitivity, although the throughput was lowered since a sample had to be added to several spots for multiple measurements, which meant that Asano's device took four-times longer than either Mentele's or ours during the respective sample introductions.…”
Section: Calibration Curvesupporting
confidence: 87%
See 1 more Smart Citation
“…The limit of quantification (LOQ) was estimated at 40 ppm, which was the minimum concentration that could be distinguished by the image processing software when the threshold of the color intensity was adjusted to the minimum value of zero, which was the intensity of the blank. The LOQ was comparable to that reported by Mentele et al 16 (1.5 μg in 30 μL, 50 mg L -1 ) while Asano et al found a lower LOQ (13.8 μM, 0.771 mg L -1 ) using a paper device with test spots where no diffusion happened since a single spot was used as a reservoir. 23 Thus, the spot-type paper device was preferable for enhancing the sensitivity, although the throughput was lowered since a sample had to be added to several spots for multiple measurements, which meant that Asano's device took four-times longer than either Mentele's or ours during the respective sample introductions.…”
Section: Calibration Curvesupporting
confidence: 87%
“…4,5 μPADs have shown promise for their use in point-of-care testing during bioanalysis, as described in many publications. [6][7][8][9][10][11][12][13][14][15][16] When used in environmental analysis, μPADs have been successfully applied to the measurement of metal ions in particulate matters (PMs), [17][18][19] as well as being useful for measuring the oxidative activity of PMs. 20 We also reported the rapid use of μPADs in acid-base titrations during the on-site analysis of acidic water in a natural hot spring.…”
Section: Introductionmentioning
confidence: 99%
“…The LOD obtained by our developed method was lower than that observed for a similar assay performed on μPADs. [16][17][18] Designing such devices was not only complex, but also required higher analyte volumes and longer durations for completion of the assay. On the other hand, our setup is easy with the one-step addition of the analyte to the reagent area/spot.…”
Section: One-step Assay For Fe 2+ Ionsmentioning
confidence: 99%
“…Among POCT devices, paper-based devices have been seen as the ideal platform for point-of-care (POC) diagnostics due to their very low cost, simplicity, and inherent ability to wick fluids. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Fluid transport eliminates expensive pumping instrumentation and complicated handling. 16,17 The porous structure of paper is very convenient for dot-immunobinding assays, and cellulose itself has high affinity to biomolecules.…”
Section: Introductionmentioning
confidence: 99%